Nematode parasites of invertebrates from Manipur, North East India (Diagnosis, keys and illustration) - Shah, M. Manjur; Mohilal, N.; Pramodini, M.; Bina, L.; Hemananda, Th. (Zootaxa, 2011)
The present report is based on findings of occasional survey work conducted from the region spanning over six years for the presence of insect parasitic nematodes under the superfamily Thelastomatoidea (Nematoda: Oxyurida), parasitic in invertebrate hosts. Out of five families recognized under the superfamily, the present report discusses the findings of four families from Manipur and its adjoining areas as well. For the first time, out of 15 taxa described in the text, seven species are described from the region, eight species reported. The findings of the study will help in understanding of the biodiversity status of insect parasitic nematodes of the region. Diagnosis of the genus, key to species and illustration with line diagrams and photomicrographs are provided in the manuscript.